Desain Formulasi Lumpur Untuk Pemboran Panas Bumi Di Sumur GG-01 - Nugroho Marsiyanto; Wahyu Sutresno; Berkah Hani (Jurnal Bhara Petro Energi, 2025)
During the drilling process, we need to look at several aspects that need to be considered, including  the  drilling  mud  aspect  which  is  one  of  the  important  aspects  in  a  safe  and  efficient drilling process.The success of a drilling process through various rock layers is very dependent on  the  design  of  the  drilling  mud  formulation.  All  of  that  can  be  influenced  by  the  nature  and physics  of  the  drilling  mud  which  needs  to  be  adjusted  to  the  formation  conditions,  formation pressure, rock type and fluid content contained in the formation. In designing the mud formulation that will be used, it can be done by using the mud system correlation method or by analyzing the pressure  wells  that  become  offset  wells  or  key  wells  which  are  analyzed  to  determine  the properties of the mud to be used. Well GG – 01 is an exploration well so it does not have an offset well. The drilling that will be penetrated is as many as 4 routes which in the first route the hole is made using a mash system so that it does not use drilling mud. And for the next route, the type of mud to be used is KCL Polymer with a different percentage on each route.